Artificial intelligence-powered microfluidics for nanomedicine and materials synthesis. Issue 46 (23rd November 2021) - Liu, Linbo; Bi, Mingcheng; Wang, Yunhua; Liu, Junfeng; Jiang, Xiwen; Xu, Zhongbin; Zhang, Xingcai
Abstract : Artificial intelligence-powered microfluidics has greatly promoted the development of nanomedicine and material synthesis. Abstract : Artificial intelligence (AI) is an emerging technology with great potential, and its robust calculation and analysis capabilities are unmatched by traditional calculation tools. With the promotion of deep learning and open-source platforms, the threshold of AI has also become lower. Combining artificial intelligence with traditional fields to create new fields of high research and application value has become a trend. AI has been involved in many disciplines, such as medicine, materials, energy, and economics. The development of AI requires the support of many kinds of data, and microfluidic systems can often mine object data on a large scale to support AI. Due to the excellent synergy between the two technologies, excellent research results have emerged in many fields. In this review, we briefly review AI and microfluidics and introduce some applications of their combination, mainly in nanomedicine and material synthesis. Finally, we discuss the development trend of the combination of the two technologies.